ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI SISTEM INFOMASI PUBLIKASI LAYANAN DATA ONLIN MENGGUNAKAN METODE SERVICE QUALITY (SERVQUAL) DI BADAN PUSAT STATISTIK PROVINSI SUMATERA BARAT (BPS PROV SUMBAR) - Agung Gemilang; Zulhendra Zulhendra; Yeka Hendriyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
System Information  as a support facility within an institution that is intended to simplify the task of the user, so as to achieve time, cost, and resource saving in decision making. User satisfaction of  System information is one factor or measure of success for any development and implementation of System Information in agency or company. A good Service quality image can be viewed from the point of view or perception  user of the System Information which is the overall assessment of the superiority of a service. This research will analyze the influence of tangibels, reliabillity, responsivenness, communication, understanding the costumers, and Access to the user  satisfaction with system information. Object of this study is the user data in the publication services of the Badan Pusat Statistik Provinsi Sumatera Barat  that uses information systems in search of required data. The results of this study indicate that simultaneously and partially there is a significant influence between variable x with user satisfaction (Y). While the results of the analysis of the level of achievement of respondents to each variable, variable X5 (Access) become a variable that is very influential on the level of user satisfaction, is 92.5% is categorized as a strong variable. Keywords: Service Quality, gap , System Information